2008
DOI: 10.1007/s00449-008-0256-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and acetate production by Clostridium ljungdahlii and Clostridium autoethanogenum using resting cells

Abstract: Combined gasification and fermentation technologies can potentially produce biofuels from renewable biomass. Gasification generates synthesis gas consisting primarily of CO, CO(2), H(2), N(2), with smaller amounts of CH(4), NO(x), O(2), C(2) compounds, ash and tars. Several anaerobic bacteria species can ferment bottled mixtures of pure synthesis gas constituents. However, there are challenges to maintaining culture viability of synthesis gas exposed cells. This study was designed to enhance culture stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 31 publications
2
70
0
1
Order By: Relevance
“…autoethanogenum was isolated from rabbit faeces in 1994 and has a reported ideal growth temperature of 37 °C [160]. Minimal research was done on C. autoethanogenum as a gas fermenting organism until the past five years when it has undergone research for the production of ethanol with synthesis gas or pure carbon monoxide as feedstock [161][162][163][164]. Only low-level ethanol production of 0.32 g L [163] has been reported for this strain, with CO as the sole carbon source.…”
Section: Ethanol Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…autoethanogenum was isolated from rabbit faeces in 1994 and has a reported ideal growth temperature of 37 °C [160]. Minimal research was done on C. autoethanogenum as a gas fermenting organism until the past five years when it has undergone research for the production of ethanol with synthesis gas or pure carbon monoxide as feedstock [161][162][163][164]. Only low-level ethanol production of 0.32 g L [163] has been reported for this strain, with CO as the sole carbon source.…”
Section: Ethanol Productionmentioning
confidence: 99%
“…It has been hypothesised that non-growth-promoting conditions will improve the production profile, with solventogenesis favoured when cells are in the resting state [164]. This can be induced through transferring the cells to nutrient-limited media; for example, Cotter et al found that nitrogen limitation led to improved ethanol production in C. autoethanogenum [164].…”
Section: Fermentation and Bioreactor Optimisationmentioning
confidence: 99%
“…Strain and culture conditions C. ljungdahlii DSM 13528 was purchased from a German collection of microorganisms and cell cultures (DSMZ, Braunschweig, Germany) and was grown anaerobically under the following five tested conditions in PETC medium (17) at 37 C (in triplicate): (i) 5 g/l of fructose as the sole carbon source, (ii) syngas (CO: CO 2 , 4:1, 1.6 atm) as the sole carbon source, (iii) 5 g/l of fructose supplemented with 0.5% ethanol, (iv) 5 g/l of fructose supplemented with 2% 2, 3-butanediol, and (v) 5 g/l of fructose supplemented with 0.25% butanol.…”
Section: Methodsmentioning
confidence: 99%
“…ljungdahlii DSM 13528 fixes CO and CO 2 through the WoodLjungdahl pathway and converts syngas into acetyl-CoA, a precursor for the production of many useful chemicals, such as ethanol (17), acetate (18), butanol (19), 2,3-butanediol (20) and other byproducts. The solvents generated by C. ljungdahlii DSM 13528 are autotoxic, and thus, the strain has evolved mechanisms to acclimate to these stresses (19,20).…”
mentioning
confidence: 99%
“…Continuous stirred tank reactors, bubble columns, packed columns, air-lift, trickle beds and hollow fiber reactors are some of the bioreactor configurations studied for alcohol production using syngas fermentation (Datar et al, 2004;Hickey et al, 2011;Kimmel et al, 1991;Kundiyana et al, 2010;Mohammadi et al, 2012;Shen et al, 2014a). Further, these reactors can be operated in different fermentation modes such as batch, fed-batch, continuous with and without cell recycle (Cotter et al, 2009;Grethlein et al, 1991;Lewis et al, 2007;Maddipati et al, 2011;Phillips et al, 1993). Klasson et al (1990a) used two STRs in series and reported a 30 fold increase in ethanol productivity using C. ljungdahlii.…”
Section: Bioreactor Designmentioning
confidence: 99%